2018
DOI: 10.21276/apalm.1861
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin lymphoma with granulomas. Demystifying the dilemma

Abstract: Presence of granuloma in Hodgkin lymphoma is a common finding which is often a source of diagnostic confusion.There is no clearly defined strategy to approach this dual pathology. The present case describes a diagnostic approach using modalities like immunohistochemistry and Catridge based nucleic acid amplification test that helped reach to most likely cause of granuloma with underlying Hodgkin lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies revealed that $9% of HL cases are accompanied by non-necrotizing epithelioid granulomas. [32][33][34] The presence of epithelioid granulomas in cases with HL may reflect a host response to the tumor with favorable prognostic implications. 34,35 Limitations of the Study 1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that $9% of HL cases are accompanied by non-necrotizing epithelioid granulomas. [32][33][34] The presence of epithelioid granulomas in cases with HL may reflect a host response to the tumor with favorable prognostic implications. 34,35 Limitations of the Study 1.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgkin lymphoma is a hematopoietic neoplasm that arises from germinal center or post-germinal center B-cells. The tumor histopathology is composed of characteristic multinucleated giant cells or large mononuclear cells in an inflammatory background referred to as Hodgkin and Reed-Sternberg cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%